(untitled) (International journal of artificial intelligence, 2025)
This paper explores modern approaches used in teaching English grammar. It compares traditional rule-based instruction with modern communicative and technology-enhanced methods. The study shows how these methods increase student motivation, support communication, and develop real-life language skills.